Studi Kelayakan Energi Matahari Sebagai Pembangkit Listrik Tenaga Surya di Pulau Sabang - Muhammad Ilham Maulana; Ahmad Syuhada; Sadam Husin (Jurnal Teknik Mesin Unsyiah, 2018)
Solar power generation is a power plant that utilizes solar energy as a source of electrical energy. Electrical energy in Sabang Weh Island is currently supplied by the power plant so it needs alternative energy to increase the electricity supply. The data taken in the form of sunlight intensity, voltage and current values generated from solar panels. Three points of data collection are: Banda Aceh, Kilometers zero Sabang and BMKG data Sabang Weh Island. The highest light intensity obtained on Sabang Weh Island for 853.20 watts / m2, the highest current of 4.32 Amper and a voltage value of 17, 20 Volt